Pengaruh Enam Jenis Latihan Keseimbangan terhadap Peningkatan Keseimbangan Dinamis pada Lansia - Dwianto, Ignatius Heri; Djajanti, Cicilia Wahju; Ekawati, Nora (Universitas Baiturrahim, 2025)
The decline in dynamic balance often experienced by the elderly poses a high risk of falling. These six types of balance exercises can provide motor and sensory stimulation to the body. Motor stimulation provided in the form of muscle contractions can increase muscle strength so that it can affect dynamic balance, while sensory stimulation will improve proprioceptive function. Objective: to determine the effect of six types of balance exercises on improving dynamic balance in the elderly. Method: One group pretest posttest design with 30 elderly subjects aged 60-75 years who were given six types of balance exercises in each session was 20 minutes, 2-3 times a week up to 10 sessions. Measurement: Functional Reach Test (FRT) and Time Up and Go Test (TUG). Analysis: Normality test with Shapiro Wilk and pretest-posttest difference test with paired T-test. Results: Based on the analysis of the normality test with Shapiro Wilk on the pretest and posttest, the results obtained p>0.05 which means the data is normally distributed. Meanwhile, the analysis of the pretest-posttest difference test with paired T-test produced a dynamic balance value before and after six types of balance exercises of p<0.05 (p=0.000); and also produced a dynamic balance value before and after six types of balance exercises with TUG of p<0.05 (p=0.000). This means that there is a significant difference between before and after treatment when measured by the Functional Reach Test (FRT) and Time Up and Go Test (TUG). Conclusion: Six types of balance exercises improve dynamic balance in the elderly